AN ANNOTATED TRANSLATION OF YOUR BABY AND CHILD, FROM BIRTH TO AGE FIVE - Sari, Wati Purnama (Universitas Gunadarma, 2016)
The research aims are: (1) To find out what the problems are intranslating the book entitled